Potentiality of agricultural adsorbent for the sequestering of metal ions from wastewater - P.C. Emenike; D.O. Omole; B.U. Ngene; I.T. Tenebe (Global Journal of Environmental Science and Management)
The expensive nature of metal ions detoxification from wastewater have restricted the use of conventional treatment technologies. Cheap, alternative measures have been adopted to eliminate metal contamination, and adsorptions using agricultural adsorbents seem to be the way forward. The use of agricultural adsorbents for cadmium (II), copper (II) and lead (II) ion removal has gained more interest in literature due to the level of contamination in water bodies. This review shed lights on the removal proficiency of various low–cost agricultural adsorbent for the elimination of cadmium (II), copper (II) and lead (II) ions, considering performance, surface modification, equilibrium adsorptive studies, kinetic characteristics, coefficient of correlation (R2) and reuse. Furthermore, these agricultural adsorbents have displayed better performance when rivaled with commercial/conventional adsorbent. Observations from different adsorptive capacities presented owe their performance to surface area improvement/modification, pH of the adsorbent, ionic potential of the solution, initial concentration and elemental component of the adsorbent. However, gaps have been identified to improve applicability, sorption performance, economic viability, optimization, and commercialization of suitable agricultural adsorbents.